INTEGRATING ALTRUISM AND TECHNOLOGY ACCEPTANCE TO USE SOCIAL MEDIA AMONG PRESERVICE TEACHERS - Idawati Che Mat; Hashin Mohammad; Nor Wahiza Abdul Wahat; Mazlina Pati Khan (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Nowadays, we can see dramatic increases in the use of social media, especially among adolescents. Yet not much research is being published about what drives them to social media acceptance, especially for the learning process. Based on the technology acceptance model, researchers developed a model involving knowledge sharing and technology acceptance. The research model was supported by 209 preservice teachers who have used social media. The results have shown that the usefulness and ease of use were related positively to attitude toward the usage of social media and accounted for 25% of the variance. But knowledge sharing (altruism)was no related to attitude toward the usage of social media. On the other hand, attitude toward the usage of social media significantly influenced a social media preservice teacher’s intention to use social media explain 43% of the variance of intention to use social media.